A monoclonal Trd chain supports the development of the complete set of functional γδ T cell lineages - Hahn, Anne Maria; Vogg, Lisa; Brey, Stefanie; Schneider, Andrea; Schäfer, Simon; Palmisano, Ralf; Pavlova, Anna; Sandrock, Inga; Tan, Likai; Fichtner, Alina S.; Prinz, Immo; Ravens, Sarina; et al. (Cell Reports, 2023)
The clonal selection theory describes key features of adaptive immune responses of B and T cells. For αβ T cells and B cells, antigen recognition and selection principles are known at a detailed molecular level. The precise role of the antigen receptor in γδ T cells remains less well understood. To better understand the role of the γδ T cell receptor (TCR), we generate an orthotopic TCRδ transgenic mouse model. We demonstrate a multi-layered functionality of γδ TCRs and diverse roles of CDR3δ-mediated selection during γδ T cell development. Whereas epithelial populations using Vγ5 or Vγ7 chains are almost unaffected in their biology in the presence of the transgenic TCRδ chain, pairing with Vγ1 positively selects γδ T cell subpopulations with distinct programs in several organs, thereby distorting the repertoire. In conclusion, our data support dictation of developmental tropism together with adaptive-like recognition principles in a single antigen receptor.
CRIS-Team Scopus Importer:2023-03-24
Keywords: CP: Immunology

A novel orthotopic TCR transgenic mouse model dissects the role of antigen receptor specificity for.d T cell development and function - Hahn, Anne Maria; Schneider, Andrea; Brey, Stefanie; Vogg, Lisa; Schäfer, Simon; Winkler, Thomas (EUROPEAN JOURNAL OF IMMUNOLOGY, 2021)
CRIS-Team WoS Importer:2022-03-11

Characterisation of gamma delta T cells in murine Cytomegalovirus infection - Hahn, Anne Maria; Brey, Stefanie; Schneider, Andrea; Donaubauer, Anna-Jasmina; Ringer, Mark; Winkler, Thomas (EUROPEAN JOURNAL OF IMMUNOLOGY, 2019)
CRIS-Team WoS Importer:2019-10-08

Deciphering the role of HLA-DO in immune responses after allogeneic stem cell transplantation - Zeun, Julia; Flamann, Cindy; Neubeck, S.; Bausenwein, J.; Seyler, L.; Vogler, T.; Brey, Stefanie; Büttner-Herold, Maike; Hildner, Kai; Winkler, Thomas; Bruns, Heiko; Kretschmann, S.; et al. (ONCOLOGY RESEARCH AND TREATMENT, 2021)
CRIS-Team WoS Importer:2022-03-25

he role of Fc gamma RIIB expression on B cells for anti-DNA autoantibody development in SLE - Gleußner, Nina; Schneider, Andrea; Brey, Stefanie; Nimmerjahn, Falk; Winkler, Thomas (EUROPEAN JOURNAL OF IMMUNOLOGY, 2022)
CRIS-Team WoS Importer:2023-01-27

HLA-DO: a possible switch between GvHD and GvL effect - Zeun, J.; Neubeck, S.; Lang, Vanessa; Flamann, Cindy; Nagel, L.; Kunert, Timo; Vogler, T.; Brey, Stefanie; Hildner, Kai; Bäuerle, Tobias; Büttner-Herold, Maike; Winkler, Thomas; et al. (EUROPEAN JOURNAL OF IMMUNOLOGY, 2022)
CRIS-Team WoS Importer:2023-01-27

Siglec-15 on osteoclasts is crucial for bone erosion in serum-Transfer arthritis - Korn, Marina; Schmitt, Heike; Angermüller, Sieglinde; Chambers, David; Seeling, Michaela; Lux, Uwe; Brey, Stefanie; Royzman, Dmytro; Bruckner, Christin; Popp, Vanessa; Percivalle, Elena; Bäuerle, Tobias; et al. (Journal of Immunology, 2020)
Siglec-15 is a conserved sialic acid binding Ig-like lectin, which is expressed on osteoclasts. Deficiency of Siglec-15 leads to an impaired osteoclast development, resulting in a mild osteopetrotic phenotype. The role of Siglec-15 in arthritis is still largely unclear. To address this, we generated Siglec-15 knockout mice and analyzed them in a mouse arthritis model.We could show that Siglec-15 is directly involved in pathologic bone erosion in the K/BxN serum-Transfer arthritis model. Histological analyses of joint destruction provided evidence for a significant reduction in bone erosion area and osteoclast numbers in Siglec-152/2 mice, whereas the inflammation area and cartilage destruction was comparable to wild-Type mice. Thus, Siglec-15 on osteoclasts has a crucial function for bone erosion during arthritis. In addition, we generated a new monoclonal anti Siglec-15 Ab to clarify its expression pattern on immune cells. Whereas this Ab demonstrated an almost exclusive Siglec-15 expression on murine osteoclasts and hardly any other expression on various other immune cell types, human Siglec-15 was more broadly expressed on human myeloid cells, including human osteoclasts. Taken together, our findings show a role of Siglec-15 as a regulator of pathologic bone resorption in arthritis and highlight its potential as a target for future therapies, as Siglec-15 blocking Abs are available.
CRIS-Team Scopus Importer:2020-11-20

Vitamin D stimulates Il-15 synthesis in rodent muscle - Ewendt, Franz; Drewitz, Fabienne; Althammer, Michael; Eichler, Cosima; Brandsch, Corinna; Brey, Stefanie; Winkler, Thomas; Wilkens, Mirja R.; St-Arnaud, René; Kreutz, Marina; Stangl, Gabriele I. (Biochemistry and Biophysics Reports, 2025)
Besides its classical skeletal function, vitamin D plays a critical role in both skeletal muscle and the immune system. Interleukin-15 (IL-15), which is highly expressed, and secreted complexed with its receptor, IL-15Rα, by skeletal muscle, stimulates the development of immune cells and affects myogenesis and muscle mass. However, little is known about possible regulators of this myokine. To test whether vitamin D could be a regulator of muscle IL-15 and IL-15Rα expression, C2C12 myotubes were treated with vitamin D3 metabolites and analysis were performed in gastrocnemius muscles of rats treated with a single intraperitoneal dose of 1,25(OH)2D3. The role of VDR was investigated by siRNA technique in C2C12 myotubes and in gastrocnemius muscles of vitamin D receptor knockout (Vdr-KO) mice. Treatment of C2C12 myotubes with 1,25(OH)2D3 or 25(OH)D3 increased Il-15 gene expression in a dose-dependent manner and 1,25(OH)2D3 also moderately increased the relative Il-15 protein amount. Rats treated with a single dose of 1,25(OH)2D3 demonstrated a higher mRNA abundance of muscle Il-15 than controls. The 1,25(OH)2D3 effect on Il-15 was considerably weaker in C2C12 myotubes treated with Vdr-specific siRNA. Vdr-KO mice showed significantly lower muscle Il-15 mRNA than WT mice. Il-15Ra mRNA and Il-15/Il-15Rα protein abundance were unaffected by 1,25(OH)2D3-treatment or VDR functionality, and Cyp27b1 activity is not required for 25(OH)D3-mediated Il-15 gene expression. The results provide evidence for a regulatory role of hydroxyvitamin D3 metabolites on the Il-15 synthesis in skeletal muscle cells, which is largely mediated by the VDR.
CRIS-Team Scopus Importer:2025-01-31
Keywords: Calcitriol; Cytokine; Immune system; Immunosenescence; Muscle-immune-crosstalk; Vitamin D receptor

α-Synuclein oligomers impair neuronal microtubule-kinesin interplay. - Winner, Beate; Prots, Iryna; Brey, Stefanie; et al. (Journal of Biological Chemistry, 2013)
Early α-synuclein (α-Syn)-induced alterations are neurite pathologies resulting in Lewy neurites. α-Syn oligomers are a toxic species in synucleinopathies and are suspected to cause neuritic pathology. To investigate how α-Syn oligomers may be linked to aberrant neurite pathology, we modeled different stages of α-Syn aggregation in vitro and investigated the interplay of α-Syn aggregates with proteins involved in axonal transport. The interaction of wild type α-Syn (WTS) and α-Syn variants (E57K, A30P, and aSyn(30-110)) with kinesin, tubulin, and the microtubule (MT)-associated proteins, MAP2 and Tau, is stronger for multimers than for monomers. WTS seeds but not α-Syn oligomers significantly and dose-dependently reduced Tau-promoted MT assembly in vitro. In contrast, MT gliding velocity across kinesin-coated surfaces was significantly decreased in the presence of α-Syn oligomers but not WTS seeds or fibrils (aSyn(30-110) multimers). In a human dopaminergic neuronal cell line, mild overexpression of the oligomerizing E57K α-Syn variant significantly impaired neurite network morphology without causing profound cell death. In accordance with these findings, MT stability, neuritic kinesin, and neuritic kinesin-dependent cargoes were significantly reduced by the presence of α-Syn oligomers. In summary, different α-Syn species act divergently on the axonal transport machinery. These findings provide new insights into α-Syn oligomer-driven neuritic pathology as one of the earliest events in synucleinopathies.